(untitled)
The author has published the qasida of the poet Rahmi, and his prayer with chronostych tarih) from 1224. H. (1809/10), the manuscript of which can be found in the collection of manuscripts No. 107 of The Franciscan Monastery of Mostar. According to what this poet had said about himself in his qasida (1. and 2. bayt), he might be identifıed as the poet Rahmi Sicill-i Osmani), who died in 1223. H. (1808/9), with the supposition that the date of his death was not correct. In the fırst part of the present paper, the author gives the analysis of the qasida which consists of three parts: 1. der medh-i Mostar, 2. der medh-i nehr-i Neretva, and 3. der medh-i tarif-i cisr. The comparison of this qasida with the poems on Mostar from the 17th century, shows that Rahmi had known about the poems of the previous poets that had vvritten about this town, and that he took from them certain motifs and wxpressions. In comparison with the earlier poems, Ode to the Neretva River is a complete novelty among the poems about Mostar. There also, the poet used theological system of comparison, metaphoric comparisons, as well as the comparisons of mytoiogical and geographic character. In some bayts, however, the poet often used purely descriptive method, thereby achieving very successful realistic comparison. In the analysis of the qasida, which was written in the genre of Staedgedichte (,şehirler şiiri) - the Diwan poetry, the present author devoted special atten- tion to the toponyms of self-waming and blessing in the last bayts, which could also be found in some şehr-engiz. The prayer with chronostych, vvritten on the occasion of making of the authors sword (tarih-i seyf-i Rahmi), is full of religous and combative fervour and hatred towards the enemies of the Ottoman State. In seems as though it might have been composed as a reaction to the Russian-Turkish wars fought at that time in the Danube region. The author has presented the text of the qasida in Turkish, as well as the prayer with its translation, in the second part of his paper., number=50, journal=Prilozi za orijentalnu filologiju, year=2017, month=Jun., pages=171–190